Changing on the fly : hockey through the voices of South Asian Canadians - Szto, Courtney (New Brunswick, New Jersey : Rutgers University Press, 2020)
Hockey and multiculturalism are often noted as defining features of Canadian culture; yet, rarely are we forced to question the relationship and tensions between these two social constructs. This book examines the growing significance of hockey in Canada's South Asian communities. The Hockey Night in Canada Punjabi broadcast serves as an entry point for a broader consideration of South Asian experiences in hockey culture based on field work and interviews conducted with hockey players, parents, and coaches in the Lower Mainland of British Columbia. This book seeks to inject more "color" into hockey's historically white dominated narratives and representations by returning hockey culture to its multicultural roots. It encourages alternative and multiple narratives about hockey and cultural citizenship by asking which citizens are able to contribute to the webs of meaning that form the nation's cultural fabric.
Introduction -- Myth busting : hockey, multiculturalism, and Canada -- Narratives from the screen : media and cultural citizenship -- White spaces, different faces : policing membership at the rink and in the nation -- Racist taunts of just chirping? -- South Asian masculinities and femininities -- Hockey hurdles and resilient subjects : unpacking forms of capital -- Racialized money and white fragility : class and resentment in hockey -- Taking stock : public memory and the re-telling of hockey in Canada -- Conclusion : a commitment to the future -- Appendix A: Qualitative methodology -- AppendixB: Participant information -- Appendix C: British Columbia competitive hockey. Structure
eBooks on EBSCOhost
Keywords: Hockey -- Social aspects -- Canada; South Asians -- Canada -- Social conditions; South Asians -- Cultural assimilation -- Canada; National characteristics, Canadian; Canadians; Hockey -- Aspect social -- Canada; Sud-Asiatiques -- Canada -- Conditions sociales; Sud-Asiatiques -- Acculturation -- Canada; Canadiens; SPORTS & RECREATION -- General; Canadians; Hockey -- Social aspects; National characteristics, Canadian; South Asians -- Social conditions; Canada; Courtney Szto, assistant professor, Kinesiology, Health Studies, Queen's University, Kingston, Ontario, Social Sciences, Humanities Research Council, Canada, Women, funded researcher, intersectional justice, Relationship, Physical Cultures, social constructs, Hockey Night, multiculturalism, hockey players, parents, coaches, British Columbia, Sociology, Sports, Recreation, Asian American Studies, Race, Ethnic Studies, Asian Studies, cultural citizenship